International law frameworks - Bederman, David J. (Foundation Press Thomson/West, 2006)
In this comprehensive examination of international law, you'll find in-depth, substantive discussion supported by expert analysis and commentary, case citations, statutes, and court rules. You'll also reap the benefits of the author's experience, opinions, and insight. Representative topics include treaties, international environmental law, human rights, jurisdictional immunities, and laws of war.